ANALISIS EFISIENSI PENGGUNAAN DROP HAMMER PADA PEMBANGUNAN GEDUNG BULOG - Rika Fitriani Malla; Fitriah Fitriah; Umran Sarita (Media Konstruksi : Jurnal Ilmiah Teknik Sipil, 2018)
This research aims to know the working efficiency comparison tool drop hammer based on the time and cost of the construction of a warehouse capacity of 2000 tons of Bulog and the proximity to the village of Lalobao sub-district of Andoolo Regency South Konawe work item the Foundation pillars.Calculation analysis of time and costs on the use of drop hammer was carried out using data specifications and data tools survey results data  piling field stake with drop hammer, construction time data based on specifications, erection time data based on field data, as well as data pillar of permenit stake punch with drop hammer.The results of this research show that the Foundation work on powerboats based on specification use the drop hammer, with 42 pole obtained is 32,44, while based on the d ata field using the drop hammer time retrieved is 24,79 hours. From the results of the analysis of productivity costs that needed used the tool drop hammer retrieved results based on the specifications of the required expenses is Rp.11.354.000, based on the data field expenses are needed is Rp. 8.676.410